Structure of A-DNA in solution. - Charney, E (1987)
The structure of DNA in aqueous trifluoroethanol solutions containing more than 70% (vol/vol) trifluoroethanol, where it has been proposed to have the A-conformation, has been studied by the technique of electric linear dichroism. The data demonstrate that both linear phi X174 DNA [5386 base pairs (bp) long] and a 172-bp fragment of sea urchin 5S RNA gene are in the double-helical A-form in the alcoholic solution and that two of the important structural parameters, the base tilt and the base-pair translation along the helical axis, are the same as in the A-form structure of crystalline double-helical d(GGTATACC). Despite its molecular length, the limiting reduced dichroism (-1.41) of the phi X174 DNA in low-salt aqueous solution is near the theoretical limit (-1.50) for DNA with base planes perpendicular to the helical axis. Transformation of this DNA and also of the 172-bp fragment to the A-structure in alcohol solutions reduces the experimental value of the dichroism to about -1.04, which agrees almost exactly with the value of -1.03 calculated for the A-form crystal. The base-pair translation along the helical axis was determined from relaxation of the DNA dichroism when the electric field is turned off. The 172-bp fragment is found to have a base-pair translation of only 2.6 A in the A-structure and is thus the same as in A-DNA fibers and in the A-form oligomers crystals. We conclude from the coincidence of the base-pair translation and the apparent values of the base tilt that the A structures are identical or nearly so in the solution and solid states. Comparison of the phi X174 data with data on smaller DNA fragments and with the data on the 172-bp sea urchin gene fragment unambiguously confirms that, in aqueous solution, the experimental reduced electric dichroism of B-DNA is highly dependent on molecular length, while the dichroism of the A-DNA form in alcoholic solutions is independent of molecular length at least in the range from 172 to 5386 bp.